2017
DOI: 10.1002/jcp.26003
|View full text |Cite
|
Sign up to set email alerts
|

What role does the stress response have in congestive heart failure?

Abstract: This review is concerned with cardiac malfunction as a result of an imbalance in protein proteostasis, the homeostatic balance between protein removal and regeneration in a long remodeling process involving the endoplasmic reticulum (ER) and the unfolded protein response (UPR). The importance of this is of special significance with regard to cardiac function as a high energy requiring muscular organ that has a high oxygen requirement and is highly dependent on mitochondria. The importance of mitochondria is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…Accumulating evidences suggest a critical role of ER stress in development of cardiac diseases, thus the modulation of ER stress responses is an attractive therapeutic strategy to intervene cardiovascular and heart diseases 2,31,32 . In this study, we demonstrate the importance of PRMT1 in suppression of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggest a critical role of ER stress in development of cardiac diseases, thus the modulation of ER stress responses is an attractive therapeutic strategy to intervene cardiovascular and heart diseases 2,31,32 . In this study, we demonstrate the importance of PRMT1 in suppression of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in response to stimuli such as trauma, infection, and hypoxia, their cardiovascular functions are more easily and greatly impaired, leading to a significantly higher likelihood of acute deterioration of their cardiovascular system [ 21 ], and resulting in cardiac and pulmonary dysfunction, which can be complicated by acute heart failure [ 22 ]. Furthermore, systemic metabolic disorders and depletion during post-traumatic stress can further impair cardiac function and increase the likelihood of acute cardiac complications [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the structure and function of the remaining myocardium are disrupted, eventually leading to HF (12). The apoptosis of cardiomyocytes often occurs throughout the process of heart disease, and improvement of cardiac function largely relies on the surviving cardiomyocytes (21,22). It has been demonstrated that oxidative stress is the main cause of hypoxic and ischemic heart diseases (23,24).…”
Section: Discussionmentioning
confidence: 99%